Effect of Escherichia coli enterotoxins on macromolecular absorption. Issue 11 (November 1994) - Verma, M; Majumdar, S; Ganguly, N K; Walia, B N
Abstract : Macromolecular absorption of gliadin, a wheat protein and alpha lactalbumin, a milk protein was evaluated in control and Escherichia coli enterotoxin (heat-stable, heat-labile, and both heat-stable and heat-labile enterotoxin) treated mice. The peak concentration of gliadin and lactalbumin was two hours and three hours after their ingestion, respectively. There was also a significant increase (p < 0.01) in the absorption of both the proteins in all the three toxin treated groups compared with the control group. These results suggest that intestinal permeability and macromolecular absorption changes after E coli infection.